2009
DOI: 10.1111/j.1600-6143.2009.02791.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Procedure for Detection of Intrahepatic Transplanted Islets by Magnetic Resonance Imaging

Abstract: Islet transplantation is an effective therapy for restoring normoglycemia in type-1 diabetes, but long-term islet graft function is achieved only in a minority of cases. Noninvasive magnetic resonance imaging of pancreatic islets is an attractive option for "real-time" monitoring of graft evolution. So far, previous studies have been performed in the absence of a standardized labeling procedure and, besides a feasibility study in patients, the effectiveness and safety of various labeling approaches were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 35 publications
(52 reference statements)
0
26
0
Order By: Relevance
“…On the other hand, ferumoxide was used for the same purposes in a recent study, reporting We have shown a lack of human islet toxicity of both types of nanoparticles, with viability and in vitro glua good labeling ability of this agent (20). This apparent discrepancy can be attributed to the four to five times and resident macrophages.…”
Section: Islet Function and Viability Assessmentmentioning
confidence: 99%
“…On the other hand, ferumoxide was used for the same purposes in a recent study, reporting We have shown a lack of human islet toxicity of both types of nanoparticles, with viability and in vitro glua good labeling ability of this agent (20). This apparent discrepancy can be attributed to the four to five times and resident macrophages.…”
Section: Islet Function and Viability Assessmentmentioning
confidence: 99%
“…First, the results of this study should be reproduced in 1.5-or 3.0-T MR images of islets, although previous studies demonstrated the compatibility of SPIO-labeled islets in clinical MRI. 22 Second, the focus of this study was proof-of-concept using a rodent syngeneic intraportal islet transplantation model. Before these methods can be applied to clinical islet transplantation, the results of this study should be examined in large animals using clinically available iron oxide nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid transversal projections of the vascular bed, hypointense regions of interest (ROI) were defined as those localized within the liver tissue, that had a round or elliptical shape, and appeared in up to 3 adjacent image slices. 22 When conglomerated hypointense spots were present, the animal was excluded from the quantitative analysis of MRI findings. Results were provided as the number of ROIs and the total area of ROIs (mm 2 ).…”
Section: In Vivo Mr Imaging Of Transplanted Isletsmentioning
confidence: 99%
“…After in vitro incubation with islets, SPIO nanoparticles can be detected by electronic microscopy in the lysosomes of ÎČ cells, but also in other islet cells (α cells, ÎŽ cells, and islet macrophages), and also in the interstitial spaces around the islet cells [24][25][26][27]. The accumulation of SPIO nanoparticles in islets seems to depend on the iron and cell concentration in the culture medium and the incubation time [23].…”
Section: Spio Labeling Studiesmentioning
confidence: 97%
“…Recent studies tried to improve efficacy of islet labeling by using liposomes or polyethyleneimine [28,29]. It was shown that isolated human and rodent islets can be labeled with SPIO nanoparticles without impairing their insulin-secreting capacity or viability [24,25,27]. Evgenov et al [30] showed that the iron load, characterized by a short T2 relaxation time, was higher in pure islets compared with exocrine tissue alone.…”
Section: Spio Labeling Studiesmentioning
confidence: 97%